Sosialisasi Upaya Pencegahan Penyebaran Covid-19 melalui Pemakaian Handsanitizer di SD Negeri 136 Palembang - Apriana, Apriana; Setyawati, Dewi; Heryati, Heryati; Yuliarni, Yuliarni; Novianti, Rini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This article aims to provide socialization of efforts to prevent Covid-19. The Covid-19 outbreak has long been spreading in Indonesia for the past two years. The public needs to know some of the efforts to prevent Covid-19. One way to prevent Covid-19 infection is to wash your hands and use hand sanitizer. Many people do not understand how to wash their hands and use hand sanitizer properly, including students at SD Negeri 136 Palembang. Therefore, the Team carried out knowledge dissemination activities and provided assistance in preventing Covid-19 at Primary School 136 Palembang. This service activity is carried out through lectures and demonstrations. The result of this service is the implementation of socialization and providing counseling about hand washing and training on the use of good and correct hand sanitizers.